Knowledge, Attitude and Practices towards prevention of Anaemia among Pregnant Women aged 18- 45 years in Gulu Regional Referral Hospital, Gulu District. A Cross-sectional Study. - Katushabe , Mercy Claire; Atukuuma, Cliffe (Student's Journal of Health Research Africa, 2022)
Background: The purpose of the study was to assess the knowledge, attitude, and practices toward the prevention of anaemia among pregnant women aged 18-45 years in the Gulu regional referral hospital, Gulu district. Methodology: The study employed a cross-sectional study design with simple random sampling as the sampling technique. Data were collected on a sample size of 50 respondents using semi-structured questionnaires written in the English language with open and ended questions as data collection tools; analysis was done manually using tally sheets, pens, and paper, entered in an excel computer program; presented in tables and figures; then interpreted. Results: (94%) of respondents agreed that going for antenatal visits is important, (85%) agreed that a mother and a child can benefit from taking iron supplements, (72%) disagreed that cultural or religious beliefs prevent pregnant women from eating certain types of food, (60%) always preferred to sleep under ITNs and (70%) reported that they feel normal when they sleep under ITNs. (56%) of respondents who had attended three ANC visits, (62%) of iron supplements they had ever taken were folic acid, (68%) usually take the iron supplements, (50%) commonly feed on carbohydrates, (60%) utilize meals three times daily and (90%) receive an iron supplement from a health facility. Conclusion: The study established a research gap in regards to types of food they commonly feed on, low uptake of ITNs, ANC, and irregular iron supplements intake among a notable few women, and inadequate access to iron supplements at the hospital which needs to be addressed for equitable anaemia prevention interventions. Recommendation: Therefore, health workers at Gulu regional referral hospital should continue to sensitize pregnant women on the dangers of not sleeping under ITNs, irregular ANC visits, and iron intake which was observed.